The application of the opposability for the solution of double sale of property cases: A jurisprudential analysis - Vargas Sequeiros, Luis Diego (2022)
Cases of double sale of property are handled by the supreme court of this country with a diversity of interpretations of the Civil Code. Good faith and the correct systematic interpretation of articles 1135 and 2022 of the Civil Code are important aspects that have been overlooked over the years, despite being essential to provide a coherent solution to this problem.This article dives deeper into this issue. The author urges the development of good faith in the articles mentioned and challenges for good faith interpretation. To support his claims, the author further analyzes a variety of Supreme Court cases and appeals.